2022
DOI: 10.1136/bmjopen-2021-057701
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injury Screening Tool (BIST): test–retest reliability in a community adult sample

Abstract: ObjectiveTo determine the test–retest reliability of the Brain Injury Screening Tool (BIST), which was designed to support the initial assessment of mild traumatic brain injury (mTBI) across a variety of contexts, including primary and secondary care.DesignTest–retest design over a 2-week period.SettingCommunity based.ParticipantsSixty-eight adults (aged 18–58 years) who had not experienced an mTBI within the last 5 years and completed the BIST on two different occasions.MeasuresParticipants were invited to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…However, general health and stress were not found to impact symptom reporting in this sample. These results on mood generally align with an earlier study using the original version of the BIST, which was found in a bivariate analysis to be linked with depression and anxiety (Shaikh et al 2022). Differences in findings between the two studies on stress are likely due to the use of different measures of stress.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…However, general health and stress were not found to impact symptom reporting in this sample. These results on mood generally align with an earlier study using the original version of the BIST, which was found in a bivariate analysis to be linked with depression and anxiety (Shaikh et al 2022). Differences in findings between the two studies on stress are likely due to the use of different measures of stress.…”
Section: Discussionsupporting
confidence: 85%
“…Premorbid mental health problems (e.g. depression, anxiety) are a risk factor for prolonged recovery following mTBI (Iverson et al 2020) and are also associated with greater symptom experience in the general population (Suhr and Gunstad 2002;Iverson and Lange 2003;Zakzanis and Yeung 2011;Voormolen et al 2019;Shaikh et al 2022). There is also preliminary evidence that higher levels of stress may be linked to higher levels of physical symptom reporting, but this study was not specific to mTBI-like symptoms (Goldman et al 1996).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations